Free to fail? Paternalistic preferences in the United States - Björn Bartling; Alexander W. Cappelen; Henning Hermes; Marit Skivenes; Bertil Tungodden (University of Zurich, Department of Economics, 2023)
We study paternalistic preferences in two large-scale experiments with participants from the general population in the United States. Spectators decide whether to intervene to prevent a stakeholder, who is mistaken about the choice set, from making a choice that is not aligned with the stakeholders' own preferences. We find causal evidence for the nature of the intervention being of great importance for the spectators' willingness to intervene. Only a minority of the spectators implement a hard intervention that removes the stakeholder's freedom to choose, while a large majority implement a soft intervention that provides information without restricting the choice set. This finding holds regardless of the stakeholder's responsibility for being mistaken about the choice set - whether the source of mistake is internal or external - and in different subgroups of the population. We introduce a theoretical framework with two paternalistic types - libertarian paternalists and welfarists - and show that the two types can account for most of the spectator behavior. We estimate that about half of the spectators are welfarists and that about a third are libertarian paternalists. Our results shed light on attitudes toward paternalistic policies and the broad support for soft interventions.
Keywords: C91; C93; D69; D91; 330; paternalism; libertarian paternalism; welfarism; freedom to choose